Unmasking depression in persons attempting suicide - Soornarain S. Naidoo; Uvistra Naidoo; Ashantha Naidoo (South African Family Practice, 2015)
Background: Suicidal behaviour is highly prevalent and increasing at an alarming rate among all socio-demographic groupings in South Africa. Approximately 9.5% of all unnatural deaths in young people in South Africa are due to suicide. The ratio of non-fatal suicide attempts to attempts with fatal outcomes varies between 20:1 and 40:1 depending on the geographical region and the community composition being studied. Although depression is a common co-existing finding in many studies involving patients with suicidal behaviour, current evidence suggests that it is either not detected or it is inappropriately managed in clinical practice.